Effects of Gender Stereotypes on Career Aspirations in Adolescents in Kenya - Chebet, Elizabeth (International Journal of Psychology, 2024)
Purpose: The aim of the study was to analyze the effects of gender stereotypes on career aspirations in adolescents in Kenya. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: A study in Kenya found that gender stereotypes strongly shape adolescents' career aspirations. Boys lean towards traditionally masculine careers like engineering, while girls are inclined towards feminine roles like nursing. Societal and familial pressures also limit career choices based on gender norms. This highlights the importance of interventions to challenge stereotypes and promote gender equality in education and career opportunities. Unique Contribution to Theory, Practice and Policy: Social cognitive career theory (SCCT), social role theory & intersectionality theory may be used to anchor future studies on effects of gender stereotypes on career aspirations in adolescents in Kenya. Schools and educational institutions should implement gender-sensitive career counseling programs that challenge traditional gender stereotypes and promote diverse career options for both boys and girls. Policymakers should develop and implement inclusive education policies that promote gender equality and challenge gender stereotypes within the educational system.